Optimization concepts and applications in engineering - Belegundu, Ashok D., 1956- (Cambridge University Press, 2011)
"It is vitally important to meet or exceed previous quality and reliability standards while at the same time reducing resource consumption. This textbook addresses this critical imperative integrating theory, modeling, the development of numerical methods, and problem solving, thus preparing the student to apply optimization to real-world problems. This text covers a broad variety of optimization problems using the following: unconstrained, constrained, gradient, and nongradient techniques; duality concepts; multiobjective optimization; linear, integer, geometric, and dynamic programming with applications; and finite element based optimization. In this revised and enhanced second edition of Optimization Concepts and Applications in Engineering, the already robust pedagogy has been enhanced with more detailed explanations, an increased number of solved examples and end-of-chapter problems. The source codes are now available free on multiple platforms. It is ideal for advanced undergraduate or graduate courses and for practicing engineers in all engineering disciplines, as well as in applied mathematics"-- Provided by publisher.
Keywords: Engineering -- Mathematical models.; Engineering design -- Mathematics.; Mathematical optimization.; Engineering models.; elektronické knihy; electronic books